(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2026)
This chapter critically analyzes existing knowledge regarding parasites of cartilaginous fishes (Chondrichthyes), examining their biological diversity, ecological dynamics, and pathological consequences. Significant knowledge gaps in this field are highlighted, particularly in biodiversity hotspots like South Africa. The study reviews key parasitic groups such as copepods, cestodes, and parasitic barnacles, discussing their impact on host fish. Furthermore, strategies for preventing and managing parasitic infections are proposed to maintain the health of cartilaginous fish populations. The aim is to stimulate research and define future directions in this crucial area of marine science.